Improving Quality of Education in Extreme Adversities-The case of Libya - Aisha Nasef; Mohamed A Al-Griw; Adel El Taguri (Journal of Biology and Medicine - Peertechz Publications, 2020)
History of medical education in Libya spans over a period of 50 years. Medical education started in faculty of medicine at Benghazi in 1970, and at Tripoli in 1973. Both medical schools performed their main core function and their graduates provided good health services locally and abroad. However, the medical schools did not keep up with the immense changes that medical education experienced over the last two decades with inclusion of research and community services within their main core function [1-3],